SUBGLACIAL GEOLOGY IN COATS LAND, EAST ANTARCTICA, REVEALED BY AIRBORNE MAGNETICS AND RADAR SOUNDING - Shepherd T.; Bamber J.L.; Ferraccioli F. (My University, 2006)
During the austral summer of 2001/02 five thousand line kilometres of airborne radio echo sounding and aeromagnetic data were collected in the region of three tributaries of Slessor Glacier, East Antarctica, which drains into the Filchner Ice Shelf. Basal topography and roughness estimates were obtained from the echo sounding data, which have been combined, here, with the subglacial geological units inferred from an analysis of the aeromagnetic data. This analysis included Euler and Werner deconvolution to determine the location and depth of sills, dykes and faults. In addition, we high-pass filtered the magnetic anomaly profiles to obtain information about the near surface subglacial geology. This revealed a prominent area of low magnetic susceptibility lying in a deep topographic basin underneath the northern tributary of Slessor Glacier. Forward and inverse magnetic models indicate that this area is likely underlain by a 3 km thick sedimentary basin. Ice flow modelling suggests that this sedimentary basin influences the ice dynamics in the tributary. These results have important implications for understanding the dynamics of this and other East Antarctic flow features that may be underlain by a weak sedimentary bed. © 2006 Elsevier B.V. All rights reserved.
Keywords: AEROMAGNETICS; EAST ANTARCTICA; RADIO ECHO SOUNDING; SLESSOR GLACIER; SUBGLACIAL SEDIMENTS